Generalized fuzzy modified distribution method for generalized fuzzy transportation problem - Amirtharaj, S. Sagaya Roseline*, E.C. Henry (International Multidisciplinary Research Journal, 2011)
In this paper, a new approach is proposed to solve Generalized fuzzy transportation problem. Here for the initial solution,Generalized fuzzy Vogel’s approximation method is preferred and to find the optimum solution a new approach, Generalized fuzzy modified distribution method is developed. This new approach is applied to a numerical example and it works well.